Super formalism in regulating transactions in the Republic of Armenia. Notarization - Tavadyan, Arsen (Bulletin of Yerevan University C: Jurisprudence, 2024)
The Civil Code of the Republic of Armenia provides that all real estate transactions are subject to notarization, and all rights arising from such transactions are subject to state registration. In case of failure to comply with these formalities, the law provides for one consequence: nullity.Such regulation unjustifiably limits the turnover of real estate, effectively prohibiting the conclusion of such transactions in which the parties provide for an earlier date of occurrence of obligations than the date of transfer of real rights. In addition, such regulation provides quite wide opportunities for abuse of rights.A study of foreign legislation gives grounds to assert that a more liberal approach is intended for real estate transactions in European countries and the EAEU. As a rule, not all real estate transactions are formalized by a notary.By providing a simple written form for every transaction, the legislator can already obtain an appropriate positive result without unnecessarily limiting civil circulation. The requirement of notarization already limits this turnover, often without bringing any positive results.Using methods of comparative legal and economic analysis of law, the author proposes to provide for a simple written form of transactions for the alienation of real estate concluded between legal entities. For transactions involving citizens, provide a notarial form. For transactions on the transfer of rights to use real estate, provide for a simple written form in general, regardless of whether the parties are individuals or legal entities.By providing a simple written form for certain real estate transactions, we can, within existing regulations, achieve the same positive results as in the case of notarization, without the disadvantages associated with such verification.
Keywords: transaction; contract; state registration; notary verification; form of contract; real estate; property law; obligations law